Skill Acquisition and Entrepreneurship Development: Evidence from Business Students - Kathayat, Bhupal Bikram (Journal of Nepalese Management and Research, 2022)
Due to globalization, business education has evolved into a corresponding educational system to produce macrobiotic entrepreneurs with a high degree of independence. Besides that, some people object to business education, which surprisingly increases unemployment. Therefore, the present study was carried out to examine the impact of skill acquisition on entrepreneurship development. The quantitative research method, survey questionnaire, and convenient sampling technique were used in this study. A questionnaire-based survey was conducted among management students in the Birendranagar Municipality, Surkhet. By applying the formula prescribed by Almeda et al. (2010), 407 students were taken as the sample size. In the case of the questionnaire, two types of questions were formulated to collect demographic and variable-related responses from respondents. In this study, the researcher found that conceptual skills and technical skills have a positive and significant (CS: P-value 0.000 < 0.05; TS: P-value 0.000 < 0.05) impact on entrepreneurial development. Thus, the designed alternative hypotheses H1 and H3 were accepted. Similarly, the study found that human skills have no significant impact on entrepreneurship development (HS: P-value 0.144 > 0.05), which means that the designed alternative hypothesis H2 was rejected in this study. In addition, the present study offers valuable insights to consider on conceptual and technical skills development instruments to the students rather than human skills that foster entrepreneurial capabilities. More specifically, students, faculty members, researchers, and government agencies will benefit from the results of this study.